(untitled) (Journal of Accessibility and Design for All, 2020)
Pictograms are used in all domains of our daily life, in orientation maps in particular. They can be depicted visually or tactilely (in relief) for blind people. The problem is that these existing pictograms are not standardized. The aim of this study was to develop a range of visuotactile orientation pictograms, which would be understandable by all population including adults, children, elderly, foreigners and visually impaired people. We conducted three studies: Study 1 aimed to make sighted users (adults and children) evaluate a set of visuotactile pictograms designed initially for blind users’ in relation with their tactile capacities and mental representation. The results show that many of these pictograms proved to be too specific to be understandable by the general population. To complement these data, we analyzed the impact of colours on the understanding of pictograms by sighted users (Study 2). Finally we conducted a series of creativity workshops with sighted adults, blind adults and sighted children (Study 3) in order to generate a new set of universal visuotactile pictograms. This research contributions are twofold: From a methodological viewpoint, we experienced and observed the limitations of two approaches (top-down and bottom-up) to design universal pictograms. From a practical viewpoint, we provide a set of universal visuotactile pictograms for orientation maps. Relevance to industry: Both the methodological insights and the design results can be useful to practitioners. The new set of universal visuotactile pictograms can be used by signalists to design accessible orientation maps.